Inappropriate use of H2 blocker ranitidine in patients hospitalized in the adult emergency service observation room in an EsSalud general hospital - Vásquez Alva, Rolando (2015)
Objective: To determine H2 blocker ranitidine misuse in an adult emergency service observation room. Design: Observational crosssectional study. Setting: Emergency Service, Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Participants: Patients 14 year-old or older. Interventions: Clinical charts of 422 patients admitted to the emergency observation rooms between January and March 2011 were reviewed. Diagnosis was confronted with pertinence of ranitidine use according to clinical guidelines of stress ulcer prophylaxis. Main outcome measures: Inadequate use of ranitidine by the ASHP Report Therapeutic Guidelines on Stress Ulcer. Results: Patients were male in 49.8% (210) and female in 50.2% (212), 62.2 year-old average. Most frequent antecedent was hypertension in 24.9% and cardiovascular as classified by systems in 32.4%. Most frequent admission diagnosis was abdominal pain syndrome in 13.3%, and cardiovascular by systems in 18.6%. From patients admitted 78.9% had no recommendation of ranitidine prescription according to appropriate diagnosis. Ranitidine was administered to 63.5% (268) of patients admitted to observation; 72% (193) of ranitidine prescriptions were not recommended according to current clinical guidelines; kappa index 0,151 showed insignificant agreement. Of patients admitted with no recommendation of ranitidine 59.9% received ranitidine by the emergency medicine specialty, 63.8% by surgery and 11.8% by traumatology. Conclusions: There was ranitidine prescription misuse at Rebagliati Hospital EsSalud emergency observation room by the emergency medicine, surgery and traumatology specialties.